Pengaplikasian media sosial dalam pembelajaran akidah sebagai sarana peningkatan kualitas iman generasi Z - Ayunda, Rina Dwi (Maliki Interdisciplinary Journal, 2024)
This article discusses the importance of utilising social media for religious education as a way to raise the level of faith of Generation Z, which is crucial in the modern world. Social media is one of the products of rapid technological development and is vital for Generation Z both now and in the future. It is a useful tool to connect with others, exchange information, and foster relationships through virtual communication tools. In essence, social media is an advanced internet-based technological tool that facilitates communication and participation among many individuals. However, one of the things that contribute to moral decay and loss of faith is the information and materials found on social media. In addition to Generation Z’s dependence on social media, some members of certain generations may lose their manners and the culture of shame may diminish as a result of unfiltered social media information. The phrase "aqidah" which talks a lot about faith, is very important to solve this problem. The author addresses this problem by using aqidah learning that provides a myriad of explanations related to religion, and associating it with social media. With a social media that is rapidly becoming popular among Generation Z can effectively increase their level of faith and this can also be useful to strengthen the faith of Generation Z.